2018
DOI: 10.3390/jcm7090239
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of Traditional Chinese Medicine for Poor Semen Quality in Infertile Males

Abstract: Poor sperm quality is one of the main factors of male infertility. Traditional Chinese Medicine (TCM) has been used frequently in clinical practice in many countries to treat a wide array of infertile problems. To further understand the effects of TCM on semen quality, we retrospectively enrolled patients with male infertility and poor semen quality at the Tainan Municipal Hospital in Taiwan between 2013 and 2016. Semen quality analysis in accordance with the WHO criteria is an essential step in the evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Some studies have reported that the TCM components of Cuscuta chinensis Lam., Epimedium brevicornum Maxim., and Rehmannia glutinosa can reduce reactive oxygen species, improve sperm motility, and effectively increase pregnancy rate. [ 51 ] The other active ingredients of herbal medicine in YSTL can also give a highly balanced supply of minerals, antioxidants and nutrients. [ 43 – 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that the TCM components of Cuscuta chinensis Lam., Epimedium brevicornum Maxim., and Rehmannia glutinosa can reduce reactive oxygen species, improve sperm motility, and effectively increase pregnancy rate. [ 51 ] The other active ingredients of herbal medicine in YSTL can also give a highly balanced supply of minerals, antioxidants and nutrients. [ 43 – 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…When a man fails to produce an adequate quantity of spermatozoa and/or produces low quality spermatozoa, these spermatozoa are called sub-optimal. The generation of low quality spermatozoa minimizes the pregnancy rate [4]. These spermatozoa can be immotile or/and abnormal in shape.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of low quality spermatozoa minimizes the pregnancy rate [4]. These spermatozoa can be immotile or/and abnormal in shape.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of idiopathic oligoasthenospermia is mainly centered on experience-based therapeutic approaches, such as antioxidant and energy supplementation, which have limitations. Traditional Chinese Medicine (TCM) has certain advantages and characteristics in the treatment of idiopathic oligoasthenospermia [7,8].…”
Section: Introductionmentioning
confidence: 99%